Antibacterial Silver Nanomaterial Synthesis From Mesoflavibacter zeaxanthinifaciens and Targeting Biofilm Formation - Oves, Mohammad; Rauf, Mohd Ahmar; Hussain, Afzal; Qari, Huda A.; Khan, Aftab Aslam Parwaz; Muhammad, Pir; Rehman, Md Tabish; Alajmi, Mohammad Fahad; Ismail, Iqbal I. M. (Frontiers in Pharmacology, 2019)
Considering the significance of biological and eco-friendly nanomaterials, in the present study, we have synthesized silver nanoparticles from the exopolysaccharide of recently recovered bacterial strain CEES51 from the Red Sea coastal area of Jeddah, Saudi Arabia. 16S ribosomal RNA gene sequencing was used to characterize the isolated bacteria, and it was identified as Mesoflavibacter zeaxanthinifaciens and assigned an accession number MH707257.1 GenBank. The bacterial strain is an excellent exopolysaccharide producer and survived at hypersaline (30%) and high-temperature (50°C) conditions. The bacterial exopolysaccharides were employed for the fabrication of silver nanoparticles at room temperature. UV-visible spectrophotometer optimized the synthesized nanoparticles, and their size was determined by Nanophox particle size analyzer and dynamic light scattering. Additionally, the X-ray powder diffraction and Fourier-transform infrared spectroscopy studies also approved its crystalline nature and the involvement of organic functional groups in their formation. The synthesized nanomaterials were tested for their antibacterial and antibiofilm properties against pathogenic microorganisms Bacillus subtilis and methicillin-resistant Staphylococcus aureus. The antimicrobial property showed time, and dose-dependent response with a maximum of zone inhibition was observed at around 22 and 18 mm at a dose of 50 µg/well against B. subtilis and S. aureus and a minimum inhibitory concentration of 8 and 10 µg/ml, respectively. Furthermore, the synthesized silver nanoparticles possessed a substantial antibiofilm property and were also found to be biocompatible as depicted by red blood cell lysis assay and their interaction with peripheral blood mononuclear cells and human embryonic kidney 293 cells. Therefore, Mesoflavibacter zeaxanthinifaciens is found to be an excellent source for exopolysaccharide synthesis that assists in the silver nanoparticle production.